WEIGHTED STATISTICAL CONVERGENCE OF ORDER ? IN PARANORMED SPACES - Et, Mikail; Karakas, Murat; Cinar, Muhammed (Turkic World Mathematical Soc, 2020)
In this study, we introduce and examine the concept of weighted statistical convergence of order a in paranormed spaces. Also some relations between weighted statistical convergence of order alpha and [((N) over bar, pn), g](r)(alpha)-summability are given.
Keywords: Weighted statistical convergence; Paranormed space; Cesaro summability; Density